2009
DOI: 10.1177/156482650903000401
|View full text |Cite
|
Sign up to set email alerts
|

A Strategic Approach to the Unfinished Fortification Agenda: Feasibility, Costs, and Cost-Effectiveness Analysis of Fortification Programs in 48 Countries

Abstract: IntroductionOne-third of the world's population suffers from micronutrient deficiencies, due primarily to inadequate dietary intake. The World Health Organization (WHO) and the United Nations Food and Agriculture Organization (FAO) have identified food fortification, supplementation, nutrition education, and disease control measures as the four main strategies for improving dietary intakes [1]. Fortification-the addition of micronutrients to a processed food to improve the food's nutritional quality-is often r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 9 publications
1
47
0
Order By: Relevance
“…To date, the most comprehensive study pertaining to the economics of micronutrient food interventions identified the feasibility and cost‐effectiveness of 122 food fortification strategies in 48 countries 24 . To address the criticism that the cost estimates of previous studies are out of date, not sufficiently detailed, and lacking in rigor, the authors estimated the cost‐effectiveness analysis of micronutrient‐fortified foods in those countries by building upon an existing model 25 .…”
Section: Resultsmentioning
confidence: 99%
“…To date, the most comprehensive study pertaining to the economics of micronutrient food interventions identified the feasibility and cost‐effectiveness of 122 food fortification strategies in 48 countries 24 . To address the criticism that the cost estimates of previous studies are out of date, not sufficiently detailed, and lacking in rigor, the authors estimated the cost‐effectiveness analysis of micronutrient‐fortified foods in those countries by building upon an existing model 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Ex post results on the cost-effectiveness of biofortification are currently limited to OSP in Uganda. These results show biofortification to cost US$15-20 per DALY saved (HarvestPlus, 2010), while for the same country the cost of vitamin A sugar fortification is US$56 per DALY saved (Fiedler and Macdonald, 2009) and the cost of vitamin A supplementation is US$52 per DALY saved (WHO, 2018).…”
Section: Comparative Advantages and Cost-effectivenessmentioning
confidence: 99%
“…Taxes and duties on fortificants will significantly affect costs, unless increased demand leads to higher volume and economies of scale, and government subsidies may mitigate the costs to protect consumers. In order to ensure sustainability of a fortification program, the structure, funding, and subsidy mechanism must be defined early when planning the program …”
Section: Summary Of the Technical Presentationsmentioning
confidence: 99%
“…In order to ensure sustainability of a fortification program, the structure, funding, and subsidy mechanism must be defined early when planning the program. 32 There are multiple, potentially complementary, approaches to combat micronutrient deficiencies. Any nutritional intervention should focus on working on the structural causes of malnutrition.…”
Section: Considerations On Economic Feasibility and Regulatory Aspectsmentioning
confidence: 99%